The Relationship Between Classroom Environment, Teacher Professional Development, and Student Academic Performance in Secondary Education - Arifin, Arifin; S.S., M.Pd.K., Dr. Suryaningsih,; Arifudin, Opan (PT. BATARI EDU CALYA, 2024)
This research investigates the intricate relationships among classroom environment, teacher professional development, and student academic performance in secondary education. Recognizing the pivotal role these factors play in shaping educational outcomes, the study employs a mixed-methods approach involving surveys, interviews, and focus group discussions. The quantitative phase targets approximately 100 teachers and 150 students, using statistical analyses such as regression and structural equation modeling. Concurrently, qualitative data from interviews with 5 teachers and 5 school administrators offer deeper insights. The study's results, evaluated using PLS-SEM, reveal significant positive relationships between classroom environment and student academic performance, teacher professional development and student academic performance, emphasizing the need for inclusive and nurturing classroom spaces and comprehensive professional development programs. This research contributes nuanced insights to inform educational policies, instructional practices, and professional development initiatives in secondary education.